(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The objective of this experiment was to examine the impact of using different levels of nanopropolis to drinking water on hematological parameters and heart, liver, gizzard, spleen and bursa gland relative weights of broiler chickens. A total of 144 one-day-old, unsexed broiler chickens with an average body weight of 40 g were used. The birds were distributed into 4 treatment groups (each with 36 birds), with three replicates in each group (12 birds per replicate). The first group drank reverse osmosis (R.O) drinking water without additions (control), whereas the second, third, and fourth groups drank reverse osmosis (R.O) drinking water containing 50, 100, and 150 µl of nano-propolis per liter, respectively. Higher some hematological variables such as RBC, Hb and PCV were observed in the 3rd and 4rd treatments compared to other treatments. Some blood parameters such as MCV, MCH, MCHC, heterophils, lymphocytes, heterophils/lymphocytes ratio and relative weight of heart, liver, gizzard, spleen and bursa gland were not affected by various amounts of nano-propolis. In conclusions, the addition of 100 and 150 μl of nanopropolis per liter of drinking water were improved some blood parameters that include RBC, Hb and PCV. Nano-propolis in current study without effect on MCV, MCH, MCHC, heterophils, lymphocytes, heterophils / lymphocytes ratio and relative weight of heart, liver, gizzard, spleen and bursa gland of broiler chickens.